2002
DOI: 10.2337/diacare.25.2.353
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fructose Concentrations in Blood and Urine in Patients With Diabetes

Abstract: OBJECTIVE -To investigate fructose metabolic changes in patients with diabetes.RESEARCH DESIGN AND METHODS -Serum and urinary fructose concentrations were determined in healthy subjects (n ϭ 23) and in nondiabetic (n ϭ 23) and diabetic patients (n ϭ 26). Fructose was measured using our newly developed method, and 13 C 6 -fructose was used as the internal standard. After adding sample to a fixed amount of internal standard, ion-exchange resins and high-performance liquid chromatography pretreatments were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
175
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(188 citation statements)
references
References 21 publications
8
175
2
3
Order By: Relevance
“…[28] Fructose blood concentrations in diabetic patients and healthy human subjects are 12.0±3.8 μmol L −1 and 8.1±1.0 μmol L −1 , respectively. [29] The blood fructose concentration corresponds to 0.096% expansion over 2 h in hydrogel fibers. Another interferent, L-lactate through its α-hydroxy acids competitively binds to 3-APBA.…”
Section: Hydrogel Optical Fiber Sensorsmentioning
confidence: 99%
“…[28] Fructose blood concentrations in diabetic patients and healthy human subjects are 12.0±3.8 μmol L −1 and 8.1±1.0 μmol L −1 , respectively. [29] The blood fructose concentration corresponds to 0.096% expansion over 2 h in hydrogel fibers. Another interferent, L-lactate through its α-hydroxy acids competitively binds to 3-APBA.…”
Section: Hydrogel Optical Fiber Sensorsmentioning
confidence: 99%
“…These investigators found that improving glycemic control resulted in normalization of the serum fructose concentrations and a marked decrease in the urine excretion of fructose (13).…”
Section: Impact Of the 8-week Protocol On Glycemic Controlmentioning
confidence: 99%
“…Kawasaki et al (13) demonstrated that blood fructose concentrations were elevated 50% and urine content was more than threefold increased in patients with diabetes. These investigators found that improving glycemic control resulted in normalization of the serum fructose concentrations and a marked decrease in the urine excretion of fructose (13).…”
Section: Impact Of the 8-week Protocol On Glycemic Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidney 8-OHdG levels in diabetic rats have been reported to be increased and reduced by insulin treatment [15], implying the involvement of hyperglycemia in the formation of 8-OHdG. Under diabetic conditions, blood glucose levels increase 2 times (10 mM) or more compared to the control level (approximately 5 mM), and an excess of glucose in the blood was partially converted into fructose by an activated polyol pathway, leading to increased levels of the latter sugar [16][17][18]. On the other hand, under diabetic situations, increases in cellular store sites of iron or copper, or increased release of them from the store sites have been reported in several studies [19][20][21].…”
Section: Introductionmentioning
confidence: 99%